AB1073 D-dimer as an early marker in patients with lupus mesenteric vasculitis. (15th June 2017) - Ma, X; Feng, X; Wang, H; Hua, B; Sun, L
Abstract : Background: Gastrointestinal manifestations are common in systemic lupus erythematosus (SLE) patients. Lupus mesenteric vasculitis (LMV) is a major cause of acute abdominal pain in SLE patients. No early serum marker contributes to the diagnosis of lupus mesenteric vasculitis. Objectives: The aim of this study was to investigate clinical significance of serum D-dimer level as an early diagnosis marker of LMV patients. Methods: The 57 systemic lupus erythematosus patients were retrospectively analyzed and classified into LMV group (n=19) and Non-LMV group (n=38) between May 2010 and January 2016. The serum D-dimer level was measured on the first day after SLE patients presented acute abdomen as well as imaging, other laboratory-testing parameters, and SLEDAI during the same period. The maximum and mean D-dimer values were analyzed and compared with other potential markers for diagnosis of LMV. The correlation of D-dimer level with other potential severity markers and inflammation parameters were also studied. Results: Both maximum and mean D-dimer level on the first day of presentation of acute abdomen were significantly higher in LMV patients. The D-dimer level was correlated well with L-lactate and SLEDAI. In addition, D-dimer level was detected poor correlation with white blood cell count and C-reactive protein level. Conclusions: D-dimer level could be an effective and early serum diagnosis marker of LMV. Disclosure of Interest: None declared